Avaliação da trajetória institucional do Programa de Apoio ao Desenvolvimento Infantil (Padin) no município de Fortaleza entre os anos de 2017 e 2023 - Oliveira, Maria Dorotéa Costa de (2024)
Evaluating a public policy represents one of the most critical and significant moments in the scope of State actions. It is through this process that it is possible to determine whether the policy developed has actually achieved its objectives, observe whether the people served by it are understanding it and are effectively benefiting. This dissertation evaluates the Child Development Support Program (PADIN), developed by the Government of the State of Ceará, which serves children from birth to three years and eleven months of age, who did not have access to public or private daycare centers. The general objective of the work is to evaluate the institutional trajectory of this program in the city of Fortaleza between the years 2017 and 2023. The specific objectives are: to identify the strategies adopted by PADIN to promote child development and improve the quality of life of the children served ; investigate the advances and challenges experienced by PADIN in its implementation in the city of Fortaleza, understand how the actions developed by PADIN impact the lives of children from the perspective of Child Development Agents (ADIs) and supervisors. The methodology adopted is qualitative and descriptive research, also using field and documentary research. The perspective used is the in-depth assessment recommended by Rodrigues in his works from 2008 and 2016. The data collection instrument was a questionnaire, applied to three different audiences, technicians from the education department of the State of Ceará, the program supervisors and the ADIs stationed in Fortaleza. To compile the collected data, Bardin's Content Analysis (1977) was used. Upon reaching the end of this work, it was found that the objectives proposed at the beginning were achieved. All interviewed audiences agree that PADIN brings relevant additions to child development, thus needing to be expanded to more municipalities in the state. There are also gains in the social and interaction spheres of families, as the program carries out a permanent process of stimulating these ties. Thus, it is concluded that even though there are some limitations shown by the actors responsible for its implementation, such as little coverage in the face of repressed demand, PADIN stands out as fundamental in helping the development of children aged zero to three.